Spotlights on some electrocardiographic paradigms: How should we evaluate normal reference values of Tp-Te interval, Tp-Te dispersion and Tp-Te/QT ratio? - Yilmaz, Mucahid; Kayancicek, Hidayet; Gozel, Nevzat; Bilen, Mehmet Nail; Kurtoglu, Ertugrul; Secen, Ozlem; Keles, Fikret (Wroclaw Medical Univ, 2020)
Background: Experimental and clinical studies evaluating the Tp-Te interval and Tp-Te/QT ratio have reported conflicting data. The overlap between normal Tp-Te/QT ratios (0.17 +/- 0.02-0.27 +/- 0.06 ms) and pathological values (0.20 +/- 0.03-0.30 +/- 0.06 ms) measured in earlier studies has raised questions about this ECG measurement technique. Objectives: To analyze normal values of the Tp-Te interval, Tp-Te dispersion Tp-Te(d) and the Tp-Te/QT ratio based on electrocardiographic (ECG) assessment across sex and age groups in a healthy Turkish population. Material and methods: A total of 1,485 healthy participants (723 men) were enrolled into the study. The age of the participants ranged 17-75 years and they did not have either any cardiovascular/systemic disorders or risk factors for atherosclerosis which were detected with physical examination and laboratory tests. The Tp-Te interval, Tp-Te(d) and Tp-Te/QT ratio were determined from V1-V6 derivations. Results: For the entire study, the median Tp-Te interval was 66.0 (64.0-70.0) ms, the Tp-Te(d) was 15.0 (10.0-20.0) ms, and the Tp-Te/QT ratio was 0.18 (0.17-0.19). The Pearson's correlation test demonstrated that the Tp-Te/QT ratio significantly correlated with older age (r = 0.297; p < 0.0001), left ventricular (LV) end-diastolic diameter (LVEDD; r = 0.481; p < 0.0001), body mass index (BMI; r = 0.421; p < 0.0001), body surface area (BSA; r = 0.191; p < 0.0001), LV end-diastolic volume (LVEDV; r = 0.484; p < 0.0001), LVEDV index (r = 0.450; p < 0.0001), LV mass (r = 0.548; p < 0.0001), and LV mass index (r = 0.539; p < 0.0001). Conclusions: The reference values for Tp-Te interval, Tp-Te(d) and Tp-Te/QT ratio are associated with age, BMI, BSA, LVEDV, LVEDV index, LV mass, and LV mass index. These structural elements should be considered when using these ECG parameters for assessing repolarization inhomogeneity. These findings may guide further studies assessing healthy and diseased populations.
Keywords: Tp-Te interval; Tp-Te/QT ratio; Tp-Te dispersion; LV mass; LV mass index